How does absorptive capacity influence the origin and evolution of dynamic capabilities - Lawer, Christopher (Cranfield University, 2010)
In this thesis, I deploy a qualitative case-study method to examine the influence of a firm’s absorptive capacity of external knowledge on the origin and evolution of dynamic capabilities. First, I make an attempt to reduce some of the conceptual and definitional confusion in the dynamic capabilities literature by developing and then validating a conceptual framework for their study in the field. Second, to examine the underlying mechanisms leading to the origination and evolution of dynamic capabilities, I call on recent literature on the absorptive capacity construct that calls for more understanding of how absorptive capacity can produce and develop dynamic capabilities. I do so in the context of stated weaknesses in the absorptive capacity literature, namely that there is an R&D functional bias, a scientific and technical knowledge content bias (linked to R&D) at the expense of process knowledge, and a methodological preference for quantitative, descriptive studies. Third, with absorptive capacity as my lens – specifically potential absorptive capacity which is only concerned with the acquiring and assimilation, not the application, of new external knowledge by a firm (after Zahra and George, 2002) - I make an attempt to reveal the constituent processes of dynamic capabilities. Fourth, I discuss and reflect whether the development of absorptive capacity can be a dynamic capability in itself and what effects, if any, absorptive capacity has on existing or new dynamic capabilities and the firm’s resource base. Finally, by focusing on dynamic capabilities as processes (or the “how” of change) and absorptive capacity of knowledge of customer needs as the content (or the “what” of change) that is flowing through those processes, I make a tentative contribution to calls for the integration of the divergent research streams of strategy as process and strategy as content (Helfat with Maritan, 2007).